2012
DOI: 10.3329/bjo.v18i1.10422
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma larynx in a 10-year-old girl: a rare clinical entity

Abstract: Abstract:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Childhood and adolescent carcinoma larynx is commonly due to HPV infection in patients with malnutrition, immunedeficiency and other environmental oncogenic factors which are common epidemiological features of developing countries. We reported a case of 10 years-old malnourished girl with persistent and progressive sore throat, dysphagia, dysphonia and ultimately respiratory distress necessitating tracheostomy and nasogastric tube feeding which was staged as T 2 N 0 M 0 and biopsied under direct laryngoscopic examination and this first case of childhood carcinoma larynx ever reported in Bangladesh 9 was diagnosed histopathologically as SCC; she was referred to avail radiotherapy but could not afford availing the appropriate treatment due to different socioeconomical constrains and ultimately embraced the unfortunate fatal outcome. The management of childhood carcinoma larynx is more difficult than in adults because of aggressive nature due to delayed diagnosis, delicate pediatric anatomic structures, and long-term complications following treatment including psychosocial factors specific to adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood and adolescent carcinoma larynx is commonly due to HPV infection in patients with malnutrition, immunedeficiency and other environmental oncogenic factors which are common epidemiological features of developing countries. We reported a case of 10 years-old malnourished girl with persistent and progressive sore throat, dysphagia, dysphonia and ultimately respiratory distress necessitating tracheostomy and nasogastric tube feeding which was staged as T 2 N 0 M 0 and biopsied under direct laryngoscopic examination and this first case of childhood carcinoma larynx ever reported in Bangladesh 9 was diagnosed histopathologically as SCC; she was referred to avail radiotherapy but could not afford availing the appropriate treatment due to different socioeconomical constrains and ultimately embraced the unfortunate fatal outcome. The management of childhood carcinoma larynx is more difficult than in adults because of aggressive nature due to delayed diagnosis, delicate pediatric anatomic structures, and long-term complications following treatment including psychosocial factors specific to adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…7 Childhood and adoloscent carcinoma larynx is more commonly supraglottic carcinoma Carcinoma larynx is an old-age malignancy; the most age at presentation of carcinoma larynx is around 7 th decade. 8 In Pakistan, the lowest age reported is 20 years, in Ghana, the lowest age reported is 17 years, in Bangladesh the lowest age reported is 35 years-but recently a case of 10 years-old girl has been reported, 9 in India, the lowest age reported is 6 years-old 10 , in USA carcinoma larynx in 15 years old 1,11 child has been reported; Childhood and adolescent carcinoma larynx has been also reported in 13.5 years old, 13 years old, 12 years old, 11 years old, 9 years old, 8.5 years old, 6 years old including the first case in the 3 years old child has been reported worldwide.…”
Section: Case Reviewmentioning
confidence: 99%
“…1,2 Rehn in 1868 first reported a case of laryngeal cancers in a 3-year-old child. 3 Extensive literature search revealed that overall 91 cases of laryngeal cancers have been reported with 28 cases below 10 years and 63 cases below 15 years. 1,4 Male predominance is not seen as in adults.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Incidence in female are nearly equal to male in pediatric laryngeal cancer (female 40% in pediatric, 10% in adult cancer). 3 Risk factor include previous irradiation of papilloma, papillomatosis, malnutrition and human papilloma virus (HPV) infection. 3 Immunologic and genetic factor which drastically modify the common risk factors, such as tobacco use, previous radiation and chemical carcinogens into definite etiologies also play a role in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation